1990
DOI: 10.1063/1.103659
|View full text |Cite
|
Sign up to set email alerts
|

Role of long-lived species in pulsed hollow cathode discharges in N2

Abstract: Experiments in pulsed hollow cathode discharges demonstrate that long-lived species, with lifetime of the order of seconds, play a significant role in the formation of the discharge in nitrogen. Detailed studies show that the effect is strongest in the hollow cathode region. Similar effects are not observed in hydrogen. A simplified model of the destruction of the N2(A3Σ+u) state has been adopted to study the relevance of this level. The possible roles of the metastables in the formation of pulsed hollow catho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Pejovic et al systematically studied the memory effect in the late afterglow for inert and molecular gases [10], but most studies were performed in nitrogen [11,12]. Similar effects were observed in pulsed hollow cathode discharges [13] and spark gaps.…”
Section: Introductionmentioning
confidence: 88%
“…Pejovic et al systematically studied the memory effect in the late afterglow for inert and molecular gases [10], but most studies were performed in nitrogen [11,12]. Similar effects were observed in pulsed hollow cathode discharges [13] and spark gaps.…”
Section: Introductionmentioning
confidence: 88%
“…The pressure range covered spans from 60-400 mTorr. The discharge was operated at a repetition rate of 1 second to partially reduce the randomness in ionization growth, through the additional 0093-3813/95$04.00 0 1995 IEEE effects of metastables [9]. The discharge apparatus uses a pulse charged plate capacitor to produce a high voltage step across the electrodes with a rise time of less than 50 ns, and a selfdecay time constant of over 1 second.…”
Section: Expepjmental Detailsmentioning
confidence: 99%
“…Another important difference to consider between our experiments and atmospheric sprites is the following: whereas in sprites metastable species have a mean life of the order of millisecond [ Sentman et al ., ], in lab discharges it has been found that the N 2 (A 3 Σ u + ) metastable, for example, can last for up to 8 s in the afterglow of a discharge [ Choi et al ., ]. In superellastic collisions these metastables can transfer their energies to the electrons increasing in this way the high‐energy tail of the energy distribution function so that the electrons have enough energy to ionize the N 2 molecules.…”
Section: Discussionmentioning
confidence: 99%